A Review Exploring the Relationship Between Nursing Home Staffing and Antipsychotic Medication Use. Issue 2 (December 2015) - Mattingly, T.
Abstract Staffing level requirements for nursing homes exist at state and federal levels in the United States. While quality of care measures may include antipsychotic (AP) prescribing, the appropriate use of APs as chemical restraints in nursing homes continues to be debated. Although the two variables appear to be related, improved research methods and availability of accurate staffing data will be needed to understand causal relationships regarding AP use for facility dwelling patients.